BANTUAN CHINA BERUPA ALAT UJI CEPAT COVID-19 KEPADA FILIPINA: PERSPEKTIF DIPLOMACY AND INTERNATIONAL LOBBYING THEORY - Hayatul Khairul Rahmat; Rizkia Mutiara Ramadhani; Nurbaiti Ma'rufah; Fitri Andrianti Indah Gustaman; Siswo Hadi Sumantri; Agus Adriyanto (Jurnal Pendidikan Ilmu Sosial, 2020)
This article aims to explain the objectives to be achieved by China related to the assistance give to the Philippines and the response that the Philippines should have done in responding. This paper used the literature study method with a descriptive approach. As for the findings of this paper, related to the theory of diplomacy and international lobbying, assistance provided by China to the Philippines is a tool used to achieve China's own interests and will have an influence on subsequent policy makers regarding maritime conflicts between China and the Philippines. Steps that needed to be taken by the Philippines are to maintain diplomatic relations with China, especially in the economic field because the Philippines economy is strongly supported by China and also strengthen its territorial defense and increase Philippine intelligence activities.